Deviation Practices in Sirri Marriage in Indonesia: A Case Study of Pakuon Village, Sukaresmi Subdistrict, Cianjur Regency, West Java - Jamilah, Mila; Suciyani (Universitas Islam Negeri Alauddin Makassar, 2026)
The practice of Sirrī marriage in Pakuon Village, Sukaresmi District, Cianjur Regency, West Java, has deviated from the norm because there are couples who have entered into Sirrī marriages between different religions and same-sex couples. The practice of Sirrī marriage has become cultural and is tolerated by religious and state leaders. The deviant practice of Sirrī marriage also highlights the motives, patterns, and impacts on legal certainty and social life. This study aims to create a society that is capable of implementing religious law and does not violate state law. This study uses Anthony Giddens' structuration theory and employs a qualitative field method with descriptive analysis. The results of this study show that Sirrī marriage makes it easier for couples to enter into interfaith and same-sex marriages in Pakuon Village, Sukaresmi District, Cianjur Regency, West Java. Sirrī marriage has become a reason for people to gain access to free education, single status according to the state, to facilitate polygamy, and several other socio-economic factors. This practice causes deviations such as interfaith and same-sex Sirrī marriages. Religious institutions such as the Ministry of Religious Affairs and the Indonesian Ulema Council (MUI) have not sufficiently supervised the implementation of Islamic marriage laws. The absence of the state in such practices is due to the lack of reports from the community and the absence of socio-economic losses. The novelty value can be seen from the irregularities that occur, such as state registration, the involvement of customary norms and family strategies in concealing marriages for socio-economic interests. Theoretically, this research enriches socio-legal studies on the negotiation between state law, religion and local culture.